The genome sequence of the Round-winged Muslin, Thumatha senex (Hübner, 1804) - Boyes, D; Sims, I; Holland, PWH (F1000 Research Ltd, 2023)
We present a genome assembly from an individual female Thumatha senex (the Round-winged Muslin; Arthropoda; Insecta; Lepidoptera; Erebidae). The genome sequence is 810.3 megabases in span. Most of the assembly is scaffolded into 30 chromosomal pseudomolecules, including the W and Z sex chromosomes. The mitochondrial genome has also been assembled and is 15.5 kilobases in length.